Results of Performance Analysis of Advanced Inftheo New Package for R - Narek S. Pahlevanyan; Haroutunian. Mariam E. (Изд-во НАН РА)
The authors have developed a new package "Advanced Inftheo" [1] for R to perform computations of complex information-theoretical results. For achieving higher computational speed, the package includes different types of parallelization. For evaluation of package performance various experiments were conducted. The analysis of these experiments are presented in this paper. Moreover, the advantages of Advacned Inftheo package compared with the existing Infotheo package are introduced.
Keywords: Mathematics